The magic of small-molecule drugs during ex vivo expansion in adoptive cell therapy - Zhang, Hanwen; Passang, Tenzin; Ravindranathan, Sruthi; Bommireddy, Ramireddy; Jajja, Mohammad Raheel; Yang, Lily; Selvaraj, Periasamy; Paulos, Chrystal M.; Waller, Edmund K. (Frontiers in Immunology, 2023)
In the past decades, advances in the use of adoptive cellular therapy to treat cancer have led to unprecedented responses in patients with relapsed/refractory or late-stage malignancies. However, cellular exhaustion and senescence limit the efficacy of FDA-approved T-cell therapies in patients with hematologic malignancies and the widespread application of this approach in treating patients with solid tumors. Investigators are addressing the current obstacles by focusing on the manufacturing process of effector T cells, including engineering approaches and ex vivo expansion strategies to regulate T-cell differentiation. Here we reviewed the current small-molecule strategies to enhance T-cell expansion, persistence, and functionality during ex vivo manufacturing. We further discussed the synergistic benefits of the dual-targeting approaches and proposed novel vasoactive intestinal peptide receptor antagonists (VIPR-ANT) peptides as emerging candidates to enhance cell-based immunotherapy.